The Relation Between Pragmatic Awareness and Realization of Requests Among Non-Native English Instructors - Anisatu Suriya, Hanny; Sofwan, Ahmad (English Education Journal, 2017)
Language acquisition requires the learners to develop their pragmatic competence so that they are able to comprehend and produce the language as a mean of conveying meaning that is understandable by certain strategy or manner. Foreign language learners with lack of pragmatic awareness realized inappropriate target language. This study, therefore, was aimed to describe the English instructors’ pragmatic awareness and realization in requests, and how the awareness relates to the realization. The study used a descriptive qualitative in order to describe and elaborate the pragmatic awareness and realization of request speech acts among the 12 representations of non-native English instructors studying English Education in Graduate Program of State University of Semarang. Multiple Discourse Completion Task (MDCT) and role play were used in collecting data. Triangulation that included English native speaker’s analysis was also used in order to enhance the validity of the data. The result of the study shows that the participants’ awareness was high in the term of power relation but lower in ranking of imposition and social distance. Power relation was the social factor that mostly influenced the choices of request strategies in the oral production of requests. It is, therefore, concluded that there is causal relation between pragmatic awareness and its realization.